Determining the Impact Factors of E-Commerce Adoption by Smes in Iraq: an Overview - T Nather, Ibrahim; A. Burhanuddin, M. (International Journal of Engineering and Technology, 2018)
The appearance for electronic commerce (e-commerce) has producedgreat benefits for enterprises; where e-commerce has become indispensable for Small and Medium Enterprises (SMEs) around the world, e-commerce is considered as an appropriate techniqueforselling, marketing and integrating online services that can play a significant role in determining, maintainingandgettingcustomers. However, e-commerce adoption staysa vital yet evasiveandcomplex phenomenon, with a quitelittle known regardingits determinants. This study aims to provide an overview of e-commerce adoption throughSMEs.Â Thatidentiï¬es the e-commerce beneï¬ts realized throughthese SMEs; an intensive review of the related literature was conducted to cover the variables of this study. The study was performed utilizing a non-experimental study exploratory research design. This exploratory study included an essential investigation about secondary data. The study development and modeling of secondary data in order to highlight the final results of the research. Through reviewing the literature of the existing frameworks and models in e-commerce adoption.Therefore, it is recommended for future researchers to conduct a field survey by collecting primary data and conducting statistical tests on the critical factors that help to adopt e-commerce in Iraqi SMEâ€™s.Â Â